Strategic Supply Chain Planning of Regional Development in Increased External Instability Conditions - Ekaterina Milovanova; Vladimir Molodyh; Irina Morozova; Elena Ostapenko (International Journal of Supply Chain Management, 2018)
A major factor in the development of a long-term supply chain strategy for social and economic development is the reduction of the shadow economy volume with the aim to increase the promising incomes of the budgetary system for most Russian Federation subjects, which have low economic potential, a small local market and limited opportunities for economic growth on their own resource base. In this regard, the regional strategic supply chain planning, taking into account the influence of the shadow economy, requires the development of adequate forecast models that take into account the specifics of the territorial processes and ensure the achievement of the target condition for the balance of socio-economic development and the achievement of the planned indicators. Two scenarios are considered in the proposed development strategy of the Russian Federation subject. Conservative scenario presupposes the development of a region on the basis of existing competitive advantage use and supply chain planning. The second scenario is based on the shadow economy negative impact reduction. General scenario conditions are formed depending on the opportunities of investment activity growth by ensuring the transparency of business rules, tax legislation stabilization and economic and investment activity increase at the expense of legal entrepreneurs. The results of the modeling show that the growth of the economy legal segment in the short term based on supply chain will lead to the reduction of employed number, but it will ensure the growth rate of labor productivity at the level of 7% per year, while the level of investment activity will grow by about 10% per year additionally. Keywords: strategic supply chain planning, shadow economy, economic growth, state regulation, regional development.